2017
DOI: 10.1002/jmor.20672
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gastrointestinal morphology of Tachyoryctes splendens (Rüppell, 1835) and Heliophobius emini, (Noack, 1894) two species of East African mole‐rats

Abstract: Tachyoryctes splendens (Northeast African mole-rat) and Heliophobius emini (Emin's mole-rat) are two African mole-rats that represent separate allopatric rodent families namely Spalacidae and Bathyergidae respectively. While these species consume a similar diet of underground plant storage organs such as roots and tubers, T. splendens has been reported to additionally consume small amounts of aerial foliage. This study aims to provide detailed gross morphological and histological morphometric analyses of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Aethomys chrysophillu s was the most distantly related to the other three species yet displayed few statistically significant morphometric differences. Therefore, the significant differences in morphometric analysis between the four species are unlikely to be caused by phylogeny as suggested in previous research on more distantly related species (Pereira et al, ; Sahd et al, ). Clearly, herbivorous rodent traits, namely a hemiglandular stomach and hindgut specialization, were similarly present in all four species, while typical insectivorous GIT traits such as a simple glandular stomach and the absence of a cecum or hindgut specialization were not represented.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Aethomys chrysophillu s was the most distantly related to the other three species yet displayed few statistically significant morphometric differences. Therefore, the significant differences in morphometric analysis between the four species are unlikely to be caused by phylogeny as suggested in previous research on more distantly related species (Pereira et al, ; Sahd et al, ). Clearly, herbivorous rodent traits, namely a hemiglandular stomach and hindgut specialization, were similarly present in all four species, while typical insectivorous GIT traits such as a simple glandular stomach and the absence of a cecum or hindgut specialization were not represented.…”
Section: Discussionmentioning
confidence: 60%
“…Lymphoid tissue was found in the cecal apex of all species studied here; however, the additional narrowing of the cecal apex seen in the Rhabdomys species indicated the presence of a cecal appendix similar to that described in a wide range of mammalian species (Smith et al, ; Smith, Parker, Kotzé, & Laurin, ). A cecal appendix was previously reported in other muroid rodents, namely, voles and lemmings (Smith et al, ) as well as in certain hystricomorphic rodents, such as in Bathyergus suillus (Cape dune mole‐rat; Kotzé, Van Der Merwe, & O' Riain, ) Georychus capensis (Cape mole‐rat; Kotzé et al, ), and Heliophobius emini (Emin's mole‐rat; Sahd, Pereira, Bennett, & Kotzé, ). The lymphoid tissue seen in the present study further supports the underlying immune function of the appendix, and the narrowing may be linked to its putative role in acting as a “safe house” or reservoir for commensal bacteria in cases of loss of the normal microbiome (Bollinger, Barbas, Bush, Lin, & Parker, ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results have showed that the mucosal layer of the gastric corpus II was significantly thicker in the plateau zokor than it was in the plateau pika, and the muscular layer in other parts of the stomach was also significantly thicker in the plateau zokor than in the plateau pika. These results indicate that the unique stomach histology of the plateau zokor can not only ensure that the gastric glands secrete enough gastric acid, mucus and other substances for chemical digestion, but—as a result of the thicker muscular layer in the gastric fundus—also strengthen the contraction and peristalsis of the stomach [ 47 ], which has a strong mechanical digestion function. Furthermore, our analysis of the gastric ultrastructure of the plateau zokor confirmed that the functional cells in the gastric tissue were highly differentiated and highly matched with their high-fiber food, indicating that they have a strong digestive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many studies have examined the GIT morphology of rodents in relation to their feeding behaviour and diet, the data for Spalacidae are limited, being available only in two spalacid species: Spalax leucodon (lesser blind mole‐rat; Gorgas, 1967; Tammam et al, 2017) and Tachyoryctes splendens (northeast African mole‐rat; Sahd et al, 2017), and is lacking for C. badius . Biological studies of this species are hardly accessible due to the need for proficiency in habitat analysis and animal tracking.…”
Section: Introductionmentioning
confidence: 99%